Basic parameters of hemostasis in patients with refractory postpartum hemorrhage - D. A. Artymuk; N. A. Artymuk; T. Yu. Marochko; A. V. Atalyan; N. M. Shibelgut; N. A. Batina; V. N. Palichev; S. V. Apresyan (Фундаментальная и клиническая медицина, 2025)
Aim. To study the types of vaginal microbial communities in women with high-grade squamous intraepithelial lesion (HSIL) and those negative for intraepithelial lesion or malignancy (NILM). Materials and Methods. Between 2021 and 2023, we conducted an analysis of vaginal microbial community types among 70 women of reproductive age infected with high-risk oncogenic HPV: those with HSIL verified by cytological examination (n = 40) and those without precancerous cervical lesions (i.e., NILM, n = 30). Identification of microorganisms in the cervical mucus was identified by mass spectrometry. Results. The frequency of normal microbiota detected by the microscopic examination was 5.3-fold lower, whilst Streptococcus spp. was detected 3-fold times higher in women with HSIL compared to the NILM group (p = 0.023). Among patients with HSIL, community state type (CST) IV was the most frequent (75%), and CST IV-C1 subtype (with Streptococcus spp. as a prevailing genus) was found in 25% of cases (p = 0.132). In patients with NILM, CST IV was also the predominant type (60%) but CST IV-C2 (with Enterococcus spp. as a prevailing genus) was most frequent subtype (23.3%, p = 0.087). The prevalence of HPV type 16 and grade 2 abnormal colposcopy findings were 3.9-fold (p = 0.008) and 3.5-fold (p = 0.040) higher in women with HSIL than in NILM (p = 0.008). Conclusion. The predominant type among vaginal microbial communities in women with HSIL and NILM was CST IV, with C1 and C2 subtypes prevailing respectively in HSIL and NILM